2020
DOI: 10.3847/2041-8213/ab9a4a
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-band Radio Observation of FRB 121102 with the Deep Space Network and the Detection of Multiple Bursts

Abstract: The spectra of repeating fast radio bursts(FRBs) are complex and time-variable, sometimes peaking within the observing band and showing a fractional emission bandwidth of about 10%-30%. These spectral features may provide insight into the emission mechanism of repeating FRBs, or they could possibly be explained by extrinsic propagation effects in the local environment. Broadband observations can better quantify this behavior and help to distinguish between intrinsic and extrinsic effects. We present results f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Our measurements agree well with estimates from the literature obtained close to our observing epochs, e.g. those from the Parkes telescope on MJD 58939 (2020 March 31) between about 0.7 to 4 GHz (Lower et al 2020a) and the one from the Deep Space Network on MJD 58947 (2020 April 08) between 2.3 and 8.4 GHz (Majid et al 2020a), which further reassured us of the fidelity of our calibration methods. The magnetar's radio spectrum was therefore surprisingly steep at the times of measurement and showed a signifi- The same multiple-epoch data as above, but plotted against frequency.…”
Section: Flux Density Timeline and Spectrumsupporting
confidence: 89%
See 1 more Smart Citation
“…Our measurements agree well with estimates from the literature obtained close to our observing epochs, e.g. those from the Parkes telescope on MJD 58939 (2020 March 31) between about 0.7 to 4 GHz (Lower et al 2020a) and the one from the Deep Space Network on MJD 58947 (2020 April 08) between 2.3 and 8.4 GHz (Majid et al 2020a), which further reassured us of the fidelity of our calibration methods. The magnetar's radio spectrum was therefore surprisingly steep at the times of measurement and showed a signifi- The same multiple-epoch data as above, but plotted against frequency.…”
Section: Flux Density Timeline and Spectrumsupporting
confidence: 89%
“…On the contrary, on the next day, MJD 58936 (2020 March 28), a single-component integrated profile was detected with high significance. We Majid et al 2020a are marked with stars. The middle panel shows a piece-wise derivative of the model frequency evolution, averaged over 1-day windows.…”
Section: 5(3) Mmentioning
confidence: 99%
“…As a result, the broadband spectral behavior of most FRBs remains largely unexplored at high frequencies since precise sky positions are generally needed for follow-up high-frequency radio observations. The precise localization of FRB121102 to a host galaxy (Chatterjee et al 2017;Marcote et al 2017;Tendulkar et al 2017) subsequently enabled the detection of numerous radio bursts up to ∼8 GHz(e.g., see Law et al 2017;Scholz et al 2017a;Gajjar et al 2018;Michilli et al 2018;Spitler et al 2018;Zhang et al 2018;Gourdji et al 2019;Houben et al 2019;Pearlman et al 2019b;Majid et al 2020). These observations revealed that FRB121102 emits narrowband bursts, with fractional emission bandwidths of ∼10-30%, across a wide range of radio frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…7 ), searching for bursts at a wide range of radio frequencies to study their spectral properties (e.g. 8,9 ), and using long-baseline interferometers to precisely localise the bursts and thereafter perform multi-wavelength follow-up to identify and study the host galaxy and local environment [10][11][12][13][14] . The repetitive nature also provides the opportunity to target these sources and record voltage data for multiple bursts -in order to probe very high time and frequency resolution, and study the polarimetric properties over a wide range of observing epochs and radio frequencies.…”
Section: Introductionmentioning
confidence: 99%